OPTIMALISASI SISTEM SIRKULASI DAN PENZONINGAN DALAM PERANCANGAN PASAR TRADISIONAL AIRMADIDI - Oley, Jessie; Warouw, Fela (Jurnal Arsitektur DASENG, 2012)
OPTIMALISASI SISTEM SIRKULASI DAN PENZONINGAN DALAM PERANCANGAN PASAR TRADISIONAL AIRMADIDI 1. Jessie Lia Oley[1]2. Fela Warouw[2] ABSTRACT Traditional Market Airmadidi located at strategic locations in the capital of the North Minahasa district. Bargaining system which is the natural advantages of the traditional market are still occured in this market. But the image of traditional markets are identical with chaotic, dirty and smelly lead an uncomfortable situation for buyers and traders. This is caused by the space and circulation paths within, has not been well-organized. Therefore, theme "Optimizing Circulation System and Zoning" has been chosen in this Airmadidi Traditional Markets design. The concept of optimizing the arrangement of space (zoning) and the circulation path is applied at the macro (site) and the micro (building mass), that produced a new design with support facilities that more well-equipped and fulfill the userâ€™s needs. Through the optimization of the circulatory system, the traditional market conditions will become more organized and comfortable, either from the circulation of vehicles, people, goods, and even between the traders and buyers. Meanwhile the optimizing of zoning system, considering the type of activity, trading medias and Â merchandise trade. Keywords: traditional market, airmadidi, optimization [1] Mahasiswa PS S1 Arsitektur Universitas Sam Ratulangi [2] Dosen Pengajar Arsitektur Universitas Sam Ratulangi